(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Case report of a pregnant woman in her 2nd trimester presenting with a tachy-arrhythmia who was non-pharmacologically cardioverted in the emergency medicine department using the modified Valsalva i.e., postural modification to the standard Valsalva and successful reversion of the same. A 35-year-old pregnant woman in her 26th week of pregnancy gravida (3), para (1), living (1), abortion (1), was brought to the emergency room with palpitations and diaphoresis. Primary survey of the patient detected an abnormally high heart rate of 216 (beats per minute) and an ECG suggestive of supraventricular tachycardia. Patient was under the criteria for a stable tachy-arrhythmia and it was decided to perform vagal manoeuvre’s expediently to cardiovert the patient, after a failed attempt at carotid massage and diving reflex. Modified Valsalva manoeuvre was performed with success. Later discharged home in good health. The aim of this article is to bring to light the importance of the emergency physician’s role in identifying tachy-arrhythmia’s, using safe, newer, effective techniques available in the armamentarium of interventions at disposal. All the more important in pregnancy due to the increased risk of adverse pregnancy outcomes (APO), that endanger the foetus and the mother and adversely impacting the prognosis off pregnancy.